2016
DOI: 10.1002/jcc.24499
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing and quantifying the torquoselectivity in competitive ring-opening reactions using the stress tensor and QTAIM

Abstract: Currently the theories to explain and predict the classification of the electronic reorganization due to the torquoselectivity of a ring-opening reaction cannot accommodate the directional character of the reaction pathway; the torquoselectivity is a type of stereoselectivity and therefore is dependent on the pathway. Therefore, in this investigation we introduced new measures from quantum theory of atoms in molecules and the stress tensor to clearly distinguish and quantify the transition states of the inward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 46 publications
1
38
0
Order By: Relevance
“…The QTAIM eigenvector trajectories T( s ) are constructed from the set of shifts dr ( s ), associated with steps s , where the parameter s is a sequence number of a given BCP in 3‐D Cartesian space as an ordered set of vectors dr ’ ( s ) in the eigenvector projection U‐space. Earlier, for a series of competitive ring‐opening reactions, some of the current authors found a BCP that moves further relative to the { e 1σ , e 2σ , e 3σ } framework at the transition state of that BCP , that is, with a longer l signifying the attainment of a lower transition state energy barrier than a BCP trajectory T σ ( s ) with a shorter l . The real‐space lengths l ( s ) of the stress tensor T( s ) and QTAIM T( s ) are calculated as the sum: l=S||bolddr()s …”
Section: Theory and Methodsmentioning
confidence: 99%
“…The QTAIM eigenvector trajectories T( s ) are constructed from the set of shifts dr ( s ), associated with steps s , where the parameter s is a sequence number of a given BCP in 3‐D Cartesian space as an ordered set of vectors dr ’ ( s ) in the eigenvector projection U‐space. Earlier, for a series of competitive ring‐opening reactions, some of the current authors found a BCP that moves further relative to the { e 1σ , e 2σ , e 3σ } framework at the transition state of that BCP , that is, with a longer l signifying the attainment of a lower transition state energy barrier than a BCP trajectory T σ ( s ) with a shorter l . The real‐space lengths l ( s ) of the stress tensor T( s ) and QTAIM T( s ) are calculated as the sum: l=S||bolddr()s …”
Section: Theory and Methodsmentioning
confidence: 99%
“…Some of the current authors also demonstrated that the ξ( r b ) is inversely related to “nearsightedness” of the first‐order density matrix and is suitable for closed‐shell systems . Recently, the use of the metallicity ξ( r b ) was demonstrated for the ring‐opening BCP . The ξ( r b ), therefore, relates to the reaction electronic flux (REF, J [ξ]) that corresponds to a chemical process along the IRC(ξ) and is defined to be J (ξ) = −d μ /dξ .…”
Section: Theory and Methodsmentioning
confidence: 99%
“…Recent studies have shown new interpretations to treat this bottleneck in electrocyclic reactions using frameworks ranging from the electron localization function (ELF), electronic structure principles, to stress tensor and QTAIM . Of these formalisms, only the stress tensor and QTAIM allowed the identification and quantification of the reaction coordinate through directional parameters, although the later was limited to use with reactions with very similar nuclear skeletons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently developed "next-generation" QTAIM (quantum theory of atoms in molecules) 9 has provided a set of tools to study the bond structure of molecular systems [4][5][6][7] , which can be used to improve our understanding of molecular switches. A recent investigation by some of the current authors 8 focussed on 3-imino-6methylenecyclohexa-1,4-diene-1,4-diamine that we referred to as the quinone switch, with F substituted in two locations (UP or DOWN) for the ring hydrogens and with and without a coordinated Fe atom above the ring, see Scheme 1.…”
mentioning
confidence: 99%